36th Bled eConference – Digital Economy and Society: The Balancing Act for Digital Innovation in Times of Instability: June 25 – 28, 2023, Bled, Slovenia, Conference Proceedings, Second Edition (University of Maribor Press, 2023)
Second edition. The Bled eConference, organised by the University of Maribor, Faculty of Organizational Sciences, has been shaping electronic interactions since 1988. The theme of the 36th conference is "Digital Economy and Society: The Balancing Act for Digital Innovation in Times of Instability". In times of instability, which include political, economic, resource, health, and environmental challenges on the one hand, and technological disruption on the other, it is critical to ensure that digital innovation continues to lead to the right and sustainable solutions that are tailored to the needs of all people, enterprises and society. It is very important to keep in mind the protection of our planet, including fauna and flora. These efforts include adopting appropriate regulatory frameworks, fostering digital literacy and skills development, promoting inclusive access to digital technologies, and addressing the ethical, social and environmental implications of digital transformation. The papers in this conference proceedings address digital transformation of enterprises, artificial intelligence and data science solutions, decision analytics for business and societal challenges, new, digital and data driven business models, digital consumer, digital education, digital health, digital ethics, restructured work and solutions for smart and sustainable cities. We continue to provide an open forum for academia, including students, industry, and policy makers where everyone can contribute to creating a better world.